Two-component solvent-free hand brush polyurea material as well as preparation method and application thereof

Through the design and preparation method of hand -brushing the polymer material with a solvent -free dual -group hand brushing material, the problem of the existing hand brushing materials cost and insufficient operating period of the existing hand brushing materials, and the high -performance and low -cost polyphon materials. It is suitable for various Construction scene.

CN119371626APending Publication Date: 2025-01-28WANHUA CHEM BEIJING

Patent Information

Application Number
CN202411479323.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hand-brushed polyurea materials have shortcomings in terms of cost and operating period and cannot be widely promoted in various fields.

Method used

Using solvent -free double -group hand brushing polymer materials, through specific raw material ratio and preparation methods, including polyether polyol, isocyanate, chain expansion agent, plasticizer, inorganic fillers, etc., forming A and B materials, and material B, and Bed, and Bed, and Bed, and B, and B, and B, and B, and B, and B, and B, and B,, and material B, and material B, and B, and B, and b Mixed and solidified by proportional during construction.

Benefits of technology

The long operation period and high physical mechanical performance of the material are realized, and the cost of material is reduced. It is suitable for different construction surfaces and does not rely on large equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096938220000141
    Figure BDA0005096938220000141
  • Figure BDA0005096938220000142
    Figure BDA0005096938220000142
  • Figure BDA0005096938220000151
    Figure BDA0005096938220000151
Patent Text Reader

Abstract

The invention provides solvent-free double-component hand brush polyurea as well as a preparation method and application thereof. The hand brush polyurea is prepared from the following raw materials: polyether polyol, thixotropic powder, isocyanate, a chain extender, a plasticizer, inorganic filler, acid and the like. The hand brush polyurea material has excellent physical and mechanical properties and permeability resistance, is long in operation period, can adjust the leveling property according to needs, and is suitable for different construction scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyurea materials, and in particular relates to a two-component solvent-free hand-brushed polyurea material and a preparation method and application thereof. Background Art

[0002] Spray polyurea was the first polyurea product to appear on the market. Its outstanding physical properties, aging resistance, and corrosion resistance led to its rapid market acceptance and widespread application. However, spray polyurea relies on large, specialized equipment for construction, making it suitable only for large sites and impractical for construction in confined areas. Furthermore, its extremely rapid curing speed poses significant challenges in integrating the material with the foundation. Hand-applied polyurea retains the excellent properties of spray polyurea while significantly extending the material's initial reaction time, allowing for sufficient construction time. This overcomes the limitations of large equipment and allows for application in confined areas. It is solvent-free, cures quickly, is insensitive to humidity and temperature, has a short construction cycle, and offers excellent high-temperature and aging resistance.

[0003] At present, the hand-brushed polyurea is commonly used in the market as the aspartame system, which has a long operation period. Workers can also roll or scrape it in places where large equipment cannot enter, but the price is high, which limits its large-scale promotion and use.

[0004] CN107955517 A discloses a polyurea-based elastomeric material for concrete protection and anti-seepage in hydraulic structures. The addition of a composite wear-resistant filler enhances the system's wear resistance and toughness. Furthermore, a multifunctional isocyanate and amino polyether rapidly cure to form a cross-linked structure, further enhancing wear resistance. This reaction yields a high-performance polyurea material, but its high reactivity limits it to spray-applied polyurea and prevents its use as a hand-applied material.

[0005] CN117586690 A discloses a two-component sprayable polyurea waterproofing material. By modifying lignin to produce a secondary amine structure, which reacts with isocyanate to produce a sterically hindered carbamate structure, the coating's reaction rate can be reduced and the operating time extended. However, this improvement in operating time is limited, with the surface-drying time remaining under 2 minutes, making it impractical for hand-scraping application.

[0006] CN110256649 A discloses a polyaspartic acid ester polyurea composite material with the advantages of low reactivity, slow reaction, and high performance. It can be constructed in restricted environments without relying on large equipment. However, the material A used is a prepolymer with an NCO% content of more than 10% and contains an aliphatic isocyanate. The polyaspartic acid ester is modified with an aliphatic chain extender, resulting in high cost. It is suitable for a limited number of high-value-added applications and cannot be widely promoted in various fields.

[0007] Therefore, it is very necessary to provide a high-performance hand-brushed polyurea material that can greatly improve the operating period and has relatively low cost. Summary of the Invention

[0008] One of the purposes of the present invention is to provide a solvent-free two-component hand-brushed polyurea. The hand-brushed polyurea material has the product advantages of aspartame polyurea, does not rely on large-scale equipment, and has significantly reduced material costs. It has a long operating period and high physical and mechanical properties. At the same time, the formula is flexible and can be easily adjusted to adapt to different construction surfaces (flat and vertical).

[0009] Another object of the present invention is to provide a method for preparing the solvent-free two-component hand-brushed polyurea.

[0010] Another object of the present invention is to provide an application of the solvent-free two-component hand-brushed polyurea.

[0011] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0012] A solvent-free two-component hand-brushed polyurea is prepared from the following raw materials in parts by weight:

[0013] 33-50 parts of polyether polyol, such as 33, 35, 38, 40, 42, 45, 47, 50 parts, etc.;

[0014] 0.1-3 parts of thixotropic powder, for example, 0.1, 0.25, 0.5, 0.7, 1, 1.2, 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3 parts, etc.;

[0015] 13-20 parts of isocyanate, for example, 13, 14, 15, 16, 17, 18, 19, 20 parts, etc.;

[0016] 7-15 parts of chain extender, for example, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts, etc.;

[0017] 3-15 parts of plasticizer, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts, etc.;

[0018] 5 to 15 parts of inorganic filler, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts, etc.;

[0019] 0.3 to 1.5 parts of wetting and dispersing agent, for example, 0.3, 0.5, 0.8, 1.0, 1.2, 1.4, 1.5 parts, etc.;

[0020] 0.1-0.5 parts of antioxidant, such as 0.1, 0.2, 0.3, 0.4, 0.5 parts, etc.;

[0021] 0.01 to 0.05 parts of catalyst, for example, 0.01, 0.02, 0.03, 0.04, 0.05 parts, etc.;

[0022] Acid 0-0.2 parts, for example, 0, 0.01, 0.03, 0.05, 0.1, 0.12, 0.13, 0.14, 0.15, 0.18, 0.2 parts, etc.

[0023] In one embodiment of the present invention, the polyether polyol is composed of at least one of polytetramethylene ether glycol and hydroxyl-terminated polyether polyol; preferably, the molecular weight of the polyether polyol is 200-7000, for example, the molecular weight is 200, 500, 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, etc., preferably 800-5000; preferably, the hydroxyl-terminated polyether polyol is polymerized from one or more of propylene oxide, ethylene oxide, tetrahydrofuran, trimethylolpropane, glycerol, ethylene glycol, and castor oil;

[0024] In one embodiment of the present invention, the isocyanate is one or more of 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and 2,4-toluene diisocyanate.

[0025] In one embodiment of the present invention, the thixotropic powder is a filler capable of forming weak hydrogen bonds to induce a thixotropic effect, preferably one or more of attapulgite, bentonite, and fumed silica.

[0026] In one embodiment of the present invention, the chain extender is an aromatic amine chain extender. Preferably, the aromatic amine chain extender is a low-activity aromatic diamine compound, preferably one or more of 4,4-bis-sec-butylaminodiphenylmethane, 3,5-diethyltoluenediamine, 3,5-dimethylthiotoluenediamine, 4,4'-bis(sec-butylamino)-diphenylmethane, and 4,4'-methylenebis(3-chloro-2,6-diethylaniline).

[0027] In one embodiment of the present invention, the boiling point of the plasticizer is higher than 130° C., and the plasticizer is preferably one or more of chlorinated paraffin, terephthalate, epoxidized soybean oil, and chlorinated palm oil.

[0028] In one embodiment of the present invention, the wetting and dispersing agent is an anti-settling dispersant, preferably one or more of a high molecular weight copolymer containing pigment affinity groups, a polycarboxylic acid ester, and a modified polysiloxane solution.

[0029] In one embodiment of the present invention, the inorganic filler is an inorganic powder with a mesh size of 400 or more, preferably one or more of calcium carbonate, kaolin, talc, white carbon black, and titanium dioxide.

[0030] In one embodiment of the present invention, the antioxidant is a hindered phenol antioxidant, preferably one or more of 3,5-di-tert-butyl-4-hydroxyphenylpropionate, 3,5-di-tert-butyl-4-hydroxyphenylpropionate, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0031] In one embodiment of the present invention, the acid has an acidity dissociation constant of less than 1.0×10 -3 Acids include one or more of phosphoric acid, oxalic acid, formic acid, acetic acid, and C3-C8 hydroxycarboxylic acids; preferably C3-C8 hydroxycarboxylic acids, more preferably one or more of lactic acid, tartaric acid, and salicylic acid.

[0032] In one embodiment of the present invention, the catalyst is an organic metal catalyst, such as an organic tin catalyst commonly used in the preparation of isocyanate, but not limited thereto.

[0033] Another aspect of the present invention is a method for preparing the aforementioned solvent-free two-component hand-brushed polyurea, the method comprising the following steps:

[0034] S1: prepolymerizing polyether polyol and isocyanate, adding an optional acid and uniformly dispersing them to obtain material A;

[0035] S2: Mix, disperse and dehydrate the chain extender, inorganic filler, plasticizer, wetting and dispersing agent, thixotropic powder, antioxidant and catalyst to obtain material B;

[0036] S3: During construction, mix material A and material B in proportion and apply by rolling or scraping. Curing under natural conditions will obtain high-strength polyurea material.

[0037] In one embodiment of the present invention, the prepolymerization temperature in S1 is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, etc., and the time is 3-6h, for example, 3h, 4h, 5h, 6h, etc.

[0038] In one embodiment of the present invention, the mass ratio of material A to material B in S3 is material A / material B = (1-2) / 1, for example, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, etc.; the R value is generally 1.05-1.5, for example, 1.1, 1.2, 1.3, 1.4, 1.5, etc.

[0039] It will be understood by those skilled in the art that other additives and other ingredients, such as color paste, defoaming agent, etc., may be added to the solvent-free two-component hand-brushed polyurea of ​​the present invention according to construction requirements.

[0040] In another aspect of the present invention, the aforementioned solvent-free two-component hand-brushed polyurea or the solvent-free two-component hand-brushed polyurea prepared by the aforementioned preparation method is used in the fields of waterproofing, flooring, anti-corrosion, etc.

[0041] In the present invention, a polyurethane prepolymer is prepared by using high-strength polyether as material A, and a certain amount of acid is added thereto; material B is based on a low-activity amine chain extender, and a portion of thixotropic powder is added to give the material low-viscosity thixotropy to prevent the powder from sinking; after the two components are mixed, the chain extender reacts with the isocyanate to generate a hard segment, which becomes the main component and improves the overall high strength of the material; the acid in material A can not only appropriately reduce the reaction speed and prolong the operation time, but also destroy the hydrogen bonds generated by the thixotropic powder in material B, causing material B to lose its thixotropy, and thus exhibit a high leveling effect as a whole, which is used for self-leveling of flat surfaces. Conversely, reducing the amount of acid used or even not adding acid can reduce the damage to the thixotropy, and is used for anti-sagging of vertical surfaces.

[0042] Compared with the prior art, the present invention has the following positive effects:

[0043] (1) Compared with spray polyurea, the product has a long operating period and can be applied by hand scraping or rolling, and can be used in various restricted scenarios;

[0044] (2) Compared with traditional hand-brushed polyurea, it breaks through the limitations of high isocyanate content and chain extension system of prepolymer, greatly reduces material cost, and provides possibilities for application in other fields;

[0045] (3) Through the correlation between acidity and thixotropy, the formula can be simply adjusted for use on different construction surfaces (flat surface, vertical surface). For example, adding relatively more acid (for example, the acid addition amount is 0.05-0.2 parts) can destroy the thixotropy of the system, improve the leveling effect, and be used for flat surface construction; adding less or no acid (for example, less than 0.05 parts) can maintain the thixotropy of the system and be used for anti-sagging on vertical surfaces. DETAILED DESCRIPTION

[0046] The principles and features of the present invention are described below in conjunction with specific embodiments. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.

[0047] The abbreviations, sources and substance names of the raw materials involved in the present invention are summarized as follows:

[0048] 3135: polyether triol with a molecular weight of 6000-6500, purchased from Wanhua Chemical Group Co., Ltd.

[0049] 2020: Polyether diol with a molecular weight of 2000, purchased from Wanhua Chemical Group Co., Ltd.

[0050] 2010: Polyether diol with a molecular weight of 1000, purchased from Wanhua Chemical Group Co., Ltd.

[0051] 2304: polyether triol with a molecular weight of 400, purchased from Wanhua Chemical Group Co., Ltd.

[0052] PTMG2000: polyether diol with a molecular weight of 2000, purchased from Wanhua Chemical Group Co., Ltd.

[0053] PTMG1000: polyether diol with a molecular weight of 2000, purchased from Wanhua Chemical Group Co., Ltd.

[0054] TDI-80: a mixture of 80% by mass of 2,4-toluene diisocyanate and 20% by mass of 2,6-toluene diisocyanate, purchased from Wanhua Chemical Group Co., Ltd.

[0055] MDI-50: a blend of 4,4'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate, purchased from Wanhua Chemical Group Co., Ltd.

[0056] Bentonite: purchased from Fengxing Chemical Trading Co., Ltd.

[0057] Attapulgite: 325 mesh, purchased from Mingmei Mineral Chemical Co., Ltd.;

[0058] E-100: 3,5-diethyltoluenediamine, purchased from Zibo Fangzhong Chemical Co., Ltd.

[0059] E-300: 3,5-dimethylthiotoluenediamine, purchased from Zibo Fangzhong Chemical Co., Ltd.

[0060] WANALINK6200: 4,4'-bis(sec-butylamino)-diphenylmethane, purchased from Wanhua Chemical Co., Ltd.

[0061] M-CDEA: 4,4'-methylenebis(3-chloro-2,6-diethylaniline), purchased from Kunshan Chemical Raw Materials Co., Ltd., Jiangsu Province;

[0062] BYK-W961: wetting and dispersing agent, propylene glycol solution of polycarboxylic acid-alkyl ammonium salt, purchased from BYK, Germany;

[0063] 7066: wetting and dispersing agent, high molecular weight polymer, purchased from Guangzhou Siloke Co., Ltd.

[0064] 1010: high molecular weight hindered phenol antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, purchased from Qingdao Haida Chemical Co., Ltd.

[0065] 1135: Liquid hindered phenol antioxidant, 3,5-di-tert-butyl-4-hydroxyphenylpropionate, purchased from Shanghai Xiuyuan Chemical Co., Ltd.

[0066] PC-03S: catalyst, zinc-bismuth composite catalyst, purchased from Shanghai Zhengui Technology Co., Ltd.

[0067] T-12: catalyst, dibutyltin dilaurate, purchased from Shanghai Minchen Chemical.

[0068] Example 1

[0069] The preparation method of hand-brushed polyurea material is as follows:

[0070] (1) After removing water, 15 g of polyether polyol 3135, 15 g of polyether polyol 2020, and 13 g of polyether polyol PTMEG1000 were placed in a reactor and heated to 50° C. Then, 18 g of MDI-50 was added and reacted at 70° C. for 3.5 h. The temperature was lowered to 65° C., 0.1 g of lactic acid was added, and the mixture was dispersed for 20 min to obtain material A.

[0071] (2) 6 g of chain extender WANALINK 6200, 5 g of chain extender E-300, 3.5 g of chlorinated paraffin, 2.7 g of epoxidized soybean oil, 6 g of talc, 0.2 g of bentonite, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0072] (3) Mix material A and material B in a mass ratio of 1.2 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 h, and take out to obtain sample 1.

[0073] Example 2

[0074] The preparation method of hand-brushed polyurea material is as follows:

[0075] (1) After dehydration, 12 g of polyether polyol 3135, 5 g of polyether polyol 2010, and 20 g of polyether polyol PTMEG2000 were placed in a reactor and heated to 55° C. Then, 13 g of MDI-50 was added and reacted at 75° C. for 3 h. The temperature was lowered to 63° C., 0.15 g of tartaric acid was added, and the mixture was dispersed for 20 min to obtain material A.

[0076] (2) 8 g of chain extender WANALINK 6200, 2 g of chain extender E-100, 5 g of DOTP, 2.2 g of calcium carbonate, 3.4 g of talc, 0.5 g of fumed silica, 0.4 g of 7066, 0.15 g of 1010, and 0.015 g of T-12 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0077] (3) Mix material A and material B in a mass ratio of 1.4 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 h, and take out to obtain sample 2.

[0078] Example 3

[0079] The preparation method of hand-brushed polyurea material is as follows:

[0080] (1) After dehydration, 12 g of polyether polyol 2020, 3 g of polyether polyol 2304, and 20 g of polyether polyol PTMEG2000 were placed in a reactor and heated to 55° C.; then 16 g of MDI-50 was added and reacted at 80° C. for 3.5 h, cooled to 60° C., 0.03 g of salicylic acid was added, and dispersed for 20 min to obtain material A;

[0081] (2) 7 g of chain extender WANALINK 6200, 5 g of chain extender M-CDEA, 5 g of chlorinated palm oil, 2.2 g of kaolin, 3.4 g of talc, 0.35 g of attapulgite, 0.5 g of BYK-W961, 0.15 g of 1010, and 0.04 g of PC-03S were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0082] (3) Mix material A and material B in a mass ratio of 1.3 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 h, and take out to obtain sample 3.

[0083] Example 4

[0084] The preparation method of hand-brushed polyurea material is as follows:

[0085] (1) After dehydration, 15 g of polyether polyol 3135, 8 g of polyether polyol 2020, and 13 g of polyether polyol PTMEG1000 were placed in a reactor and heated to 55°C; then 4 g of TDI and 9 g of MDI-50 were added and reacted at 80°C for 4.5 hours. The temperature was then lowered to 60°C, 0.1 g of lactic acid was added, and the mixture was dispersed for 20 minutes to obtain material A.

[0086] (2) 6 g of chain extender WANALINK 6200, 5 g of chain extender E-300, 3 g of chlorinated paraffin, 3 g of epoxidized soybean oil, 6 g of talc, 0.2 g of bentonite, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0087] (3) Mix material A and material B in a mass ratio of 1.3 / 1, pour 50 g into a sheet, and accelerate aging in an oven at 50°C for 48 hours. Take out and obtain sample 4.

[0088] Example 5

[0089] The preparation method of hand-brushed polyurea material is as follows:

[0090] (1) After removing water, 15g of polyether polyol 3135, 8g of polyether polyol 2020, and 13g of polyether polyol PTMEG1000 were placed in a reactor and heated to 55°C; then 4g of TDI and 9g of MDI-50 were added and reacted at 70°C for 5.5h, then cooled to 60°C, 0.13g of phosphoric acid was added, and dispersed for 20min to obtain material A;

[0091] (2) 8 g of chain extender WANALINK 6200, 5 g of chain extender M-CDEA, 4 g of chlorinated paraffin, 3 g of chlorinated palm oil, 6 g of talc, 0.2 g of bentonite, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0092] (3) Mix material A and material B in a mass ratio of 1.1 / 1, pour 50 g into a sheet, and accelerate aging in an oven at 50°C for 48 hours. Take out and obtain sample 5.

[0093] Example 6

[0094] (1) After dehydration, 15 g of polyether polyol 3135, 8 g of polyether polyol 2020, and 13 g of polyether polyol PTMEG1000 were placed in a reactor and heated to 55°C; then 4 g of TDI and 9 g of MDI-50 were added and reacted at 80°C for 4.5 hours, and then cooled to 60°C to obtain material A;

[0095] (2) 6 g of chain extender WANALINK 6200, 5 g of chain extender E-300, 3 g of chlorinated paraffin, 3 g of epoxidized soybean oil, 6 g of talc, 0.2 g of bentonite, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0096] (3) Mix material A and material B in a mass ratio of 1.3 / 1, pour 50 g into a sheet, and accelerate aging in an oven at 50°C for 48 hours. Take out and obtain sample 6.

[0097] Comparative Example 1

[0098] Compared with Example 1, the difference is that this system is a traditional spray polyurea system.

[0099] The preparation method of the polyurea material of this comparative example is as follows:

[0100] (1) 30 g of polyether polyol 3135 and 32 g of MDI-50 were reacted at 80°C for 3 h, and vacuum degassed for 0.5 h to prepare material A;

[0101] (2) 10 g of chain extender WANALINK 6200, 18 g of E-100, 50 g of D2000, and 4 g of T5000 were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated; then the temperature was lowered to 60 ° C to obtain material B;

[0102] (3) Mix material A and material B in a mass ratio of 1 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 hours, and take out to obtain sample 1#.

[0103] Comparative Example 2

[0104] Compared with Example 2, the difference is that this system is an aspartame polyurea system. The preparation method of the hand-brush polyurea material of this comparative example is as follows:

[0105] (1) 25 g of polyether polyol 3135 and 10 g of MDI-50 were reacted at 75 ° C for 2.5 h, 15 g of HT300 was added, and vacuum degassing was carried out for 0.5 h to prepare material A;

[0106] (2) 50 g of polyaspartic acid ester F420, 0.2 g of bentonite, and 50 g of talc were vacuum dehydrated at 110 ° C for 3 h until no bubbles were generated; then the temperature was lowered to 65 ° C to obtain material B;

[0107] (3) Mix material A and material B in a mass ratio of 1 / 1, pour 50 g into a sheet, accelerate aging in a 50°C oven for 48 h, and take out to obtain sample 2#.

[0108] Comparative Example 3

[0109] Compared with Example 3, the difference is that high-strength polyether is not used, and is replaced by polyether polyol 2020, and the other aspects are the same.

[0110] (1) After removing water, 32g of polyether polyol 2020 and 3g of polyether polyol 2304 were placed in a reactor and heated to 55°C; then 16g of MDI-50 was added and reacted at 80°C for 3.5h, cooled to 60°C, added with 0.05g of salicylic acid, and dispersed for 20min to obtain material A;

[0111] (2) 7 g of chain extender WANALINK 6200, 5 g of chain extender M-CDEA, 5 g of chlorinated palm oil, 2.2 g of kaolin, 3.4 g of talc, 0.35 g of attapulgite, 0.5 g of BYK-W961, 0.15 g of 1010, and 0.04 g of PC-03S were vacuum dehydrated at 120 ° C for 2 h until no bubbles were generated to obtain material B;

[0112] (3) Mix material A and material B in a mass ratio of 1.3 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 hours, and take out to obtain sample 3#.

[0113] Comparative Example 4

[0114] Compared with Example 4, the difference is that no thixotropic powder is added, and the other aspects are the same.

[0115] (1) After dehydration, 15 g of polyether polyol 3135, 8 g of polyether polyol 2020, and 13 g of polyether polyol PTMEG1000 were placed in a reactor and heated to 55°C; then 4 g of TDI and 9 g of MDI-50 were added and reacted at 80°C for 4.5 hours. The temperature was then lowered to 60°C, 0.1 g of lactic acid was added, and the mixture was dispersed for 20 minutes to obtain material A.

[0116] (2) 6 g of chain extender WANALINK 6200, 5 g of chain extender E-300, 3 g of chlorinated paraffin, 3 g of epoxidized soybean oil, 6 g of talc, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120° C. for 2 h until no bubbles were generated to obtain material B;

[0117] (3) Mix material A and material B in a mass ratio of 1.3 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 hours, and take out to obtain sample 4#.

[0118] Comparative Example 5

[0119] Compared with Example 5, the R value is kept consistent, except that no amine chain extender is used, and the other aspects are the same.

[0120] (1) After removing water, 15g of polyether polyol 3135, 8g of polyether polyol 2020, and 13g of polyether polyol PTMEG1000 were placed in a reactor and heated to 55°C; then 4g of TDI and 9g of MDI-50 were added and reacted at 70°C for 5.5h, then cooled to 60°C, 0.13g of phosphoric acid was added, and dispersed for 20min to obtain material A;

[0121] (2) 3 g of chain extender BDO, 1.8 g of chain extender DEG, 4 g of chlorinated paraffin, 3 g of chlorinated palm oil, 6 g of talc, 0.2 g of bentonite, 0.3 g of BYK-W961, 0.2 g of 1135, and 0.02 g of T-12 were vacuum dehydrated at 120° C. for 2 h until no bubbles were generated to obtain material B;

[0122] (3) Mix material A and material B in a mass ratio of 1.1 / 1, pour 50 g into a sheet, accelerate aging in an oven at 50°C for 48 hours, and take out to obtain sample 5#.

[0123] Test method:

[0124] Stability of Material B: Visual inspection: Store the prepared Material B at room temperature for one week. If there is no transparent oil seepage on the surface, no powder sedimentation at the bottom, and the system is uniform, it is stable; otherwise, it is poor.

[0125] Leveling: Visual inspection: Observe the surface flatness of the sample. If there are flow marks, it is poor; if it is smooth and flat, it is excellent.

[0126] Anti-sagging property: Visual inspection: Roll the mixed A / B materials on the facade. If there are flow marks, it is poor; if it is smooth and flat, it is excellent.

[0127] Operation period: Visual inspection: pour the mixed A / B materials into the membrane and gently scrape it with a scraper. If there is no stringing or the scratch is healed within 30 seconds, it is considered to have reached the operation period.

[0128] Tensile strength: tested according to standard GB / T 528-2009, pulling speed 500mm / min;

[0129] Waterproofness: tested according to standard GB / T 23446-2009;

[0130] Acid treatment: tested in accordance with standard GB / T 23446-2009;

[0131] Alkali treatment: tested according to standard GB / T 23446-2009;

[0132] Salt treatment: tested according to standard GB / T 23446-2009.

[0133] Table 1 Example sample performance test results

[0134]

[0135] Table 2 Performance test results of comparative samples

[0136]

[0137]

[0138] Comparative Example 1 is a traditional spray polyurea system, which cures quickly, has a very short operation period, and has no sufficient leveling time for pouring and sample preparation. In actual use, only mechanical spraying can be used.

[0139] Comparative Example 2 is an aspartame polyurea system, which has high physical properties, a decent working period, but poor leveling. In addition, the use of aliphatic isocyanate and polyaspartic acid ester in the system leads to a high overall material price, which cannot be widely popularized in the market.

[0140] Comparative Example 3 does not use high-strength polyether. Ordinary polyether cannot obtain high strength, and its physical properties are significantly reduced, which cannot meet the polyurea application standards.

[0141] Comparative Example 4 did not add thixotropic powder. The intermolecular forces between the liquid and powder were weak, making it difficult to maintain the powder's stability in the system. Long-term storage caused sedimentation, requiring re-stirring for subsequent use. Direct use risked an imbalance in the ratio, resulting in the system not solidifying or failing to meet strength standards.

[0142] Comparative Example 5 does not use a high-strength amine chain extender. Although the small molecule alcohol can obtain a longer operating period, it cannot obtain high strength, and the physical properties are significantly reduced, which cannot meet the polyurea application standards.

[0143] The physical and mechanical properties of the hand-brush polyurea of ​​the present invention far exceed the national standards, are higher than traditional spray polyurea, and are close to those of asparagus hand-brush polyurea. It does not rely on large-scale spraying equipment, can be used for construction in restricted scenarios, and can significantly reduce costs, promoting its promotion and use in other fields.

[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A solvent-free two-component hand-brushed polyurea, characterized in that: It is prepared from the following raw materials in parts by weight:

2. The hand-brushed polyurea according to claim 1, characterized in that: The polyether polyol is composed of at least two of polytetramethylene ether diol and hydroxyl-terminated polyether polyol; Preferably, the molecular weight of the polyether polyol is 200 to 7000; Preferably, the hydroxyl-terminated polyether polyol is polymerized from one or more of propylene oxide, ethylene oxide, tetrahydrofuran, trimethylolpropane, glycerol, ethylene glycol, and castor oil.

3. The hand-brushed polyurea according to claim 1 or 2, characterized in that: The thixotropic powder is a filler that can form weak hydrogen bonds to induce a thixotropic effect, and is preferably one or more of attapulgite, bentonite, and fumed silica.

4. The hand-brushed polyurea according to any one of claims 1 to 3, characterized in that: The isocyanate is one or more of 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and 2,4-toluene diisocyanate.

5. The hand-brushed polyurea according to any one of claims 1 to 4, characterized in that: The chain extender is an aromatic amine chain extender; preferably, the aromatic amine chain extender is a low-activity aromatic diamine compound, preferably one or more of 4,4-bis-sec-butylaminodiphenylmethane, 3,5-diethyltoluenediamine, 3,5-dimethylthiotoluenediamine, 4,4'-bis(sec-butylamino)-diphenylmethane, and 4,4'-methylenebis(3-chloro-2,6-diethylaniline).

6. The hand-brushed polyurea according to any one of claims 1 to 5, characterized in that: The acid has an acidity dissociation constant of less than 1.0×10 -3 The acid is selected from one or more of phosphoric acid, oxalic acid, formic acid, acetic acid, and C3-C8 hydroxycarboxylic acids; preferably C3-C8 hydroxycarboxylic acids, more preferably one or more of lactic acid, tartaric acid, and salicylic acid.

7. The hand-brushed polyurea according to any one of claims 1 to 6, characterized in that: The plasticizer has a boiling point higher than 130° C., and is preferably one or more of chlorinated paraffin, terephthalate, epoxidized soybean oil, propylene carbonate, and chlorinated palm oil; and / or, the wetting and dispersing agent is an anti-settling type dispersant, preferably one or more of a high molecular weight copolymer containing a pigment affinity group, a polycarboxylic acid ester, and a modified polysiloxane solution; And / or, the inorganic filler is an inorganic powder with a mesh size of 400 or more, preferably one or more of calcium carbonate, kaolin, talc, white carbon black, and titanium dioxide; And / or, the antioxidant is a hindered phenol antioxidant, preferably one or more of 3,5-di-tert-butyl-4-hydroxyphenylpropionate octadecyl alcohol, 3,5-di-tert-butyl-4-hydroxyphenylpropionate isooctyl, and tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol; And / or, the catalyst is an organic metal catalyst.

8. The method for preparing the solvent-free two-component hand-brushed polyurea according to any one of claims 1 to 7, characterized in that: The following steps are included: S1: prepolymerizing polyether polyol and isocyanate, adding an optional acid and dispersing them evenly to obtain material A; S2: Mix, disperse and dehydrate the chain extender, inorganic filler, plasticizer, wetting dispersant, thixotropic powder, antioxidant and catalyst to obtain material B; S3: During construction, material A and material B are mixed in proportion and applied by rolling or scraping, and cured under natural conditions to obtain a high-strength polyurea material.

9. The preparation method according to claim 8, characterized in that: The prepolymerization temperature in S1 is 70-90°C and the time is 3-6 hours.

10. Use of the solvent-free two-component hand-brushed polyurea according to any one of claims 1 to 7 or the solvent-free two-component hand-brushed polyurea prepared by the preparation method according to claim 8 or 9 in the fields of waterproofing, flooring and anti-corrosion.

Citation Information

Patent Citations

  • Polyuria-based elastomer material for protection and seepage prevention of concrete of hydraulic buildings

    CN107955517A

  • Polyaspartic acid ester polyurea composite material and preparation method thereof

    CN110256649A

  • Two-component spraying polyurea waterproof coating

    CN117586690A

  • Knife coating type polyurea waterproof coating

    CN101818018A

  • Thixotropic bi-compound polyurethane waterproof paint capable of being constructed at high temperature and preparation method thereof

    CN105331274A

Cited By

  • High-weather-resistance composite silicon PU ball scene surface layer and construction method thereof

    CN120365836A